Orbital manifestations in patients with acquired immunodeficiency syndrome - Sodhi, Punita Kumari (Nepalese Journal of Ophthalmology, 2014)
Introduction: The orbital manifestations of acquired immunodeficiency syndrome (AIDS) are uncommon. Objective: To provide a review of orbital manifestations of AIDS, the predisposing factors, investigations, treatment and outcome. Materials and methods: Meticulous and systematic literature search of Pubmed to identify manuscripts describing orbital manifestations of AIDS was done and the articles were reviewed. The keywords used in the search were “orbit and AIDS”, “HIV positive and orbit”, “orbit manifestations in AIDS”, “orbital disease and AIDS” and “orbital infections and AIDS”. The orbital involvement in AIDS may present with opportunistic infections from organisms like fungi, viruses, bacteria and protozoa or with malignancies like Kaposi’s sarcoma, squamous cell carcinoma, smooth muscle cell tumors and lymphoma. The predisposing factors for orbital involvement in AIDS are low CD4+ cell count and the immunosuppressive states like diabetes, diabetic ketoacidosis, intravenous drug abuse and neutropenia. A patient may present with fever, headache, nausea, vomiting, decreased vision, ocular pain, and, in cases of mass formation, there is periorbital swelling, axial proptosis, globe displacement and swollen optic disc. Radiologically, mass formation, orbital bony destruction, and spread of disease to contiguous structures including the central nervous system may be seen. The medical management includes therapy for infection and HIV-1 protease inhibitors (highly active antiretroviral therapy) to suppress HIV-1 replication. For tumors, radical surgery including debulking followed by postoperative radiotherapy is generally needed. Conclusion: Orbital involvements with AIDS in any form, infective or malignancy, causes significant morbidity and mortality and should be diagnosed and managed as early as possible. DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11710 Nepal J Ophthalmol 2014; 6(12): 205-219